2016
DOI: 10.1002/fsn3.360
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of nutritional properties of three species of marine turban snails for human consumption

Abstract: Turban snails (family Turbinidae) are gastropod molluscs that are harvested for human consumption yet little is known about the nutritional properties of these snails, particularly from Australian waters. This study compares the proximate composition (ash, moisture, protein, and lipid content), fatty acid profiles, mineral, and trace element content of three species of turbinid snails; Turbo militaris, Lunella undulata, and Lunella torquata from northern New South Wales, Australia. They were all found to have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 92 publications
0
16
0
6
Order By: Relevance
“…The fatty acid composition, especially PUFA contents along with DHA and EPA were previously reported in the various gastropods, particularly in the snails ( Brazao et al, 2003 , Lah et al, 2016 ). Gastropods were found to possess various minerals, such as potassium, sodium, selenium, zinc, iron, and sulfur ( Lah et al, 2016 ). Also, the essential amino acid components were considerably higher in the gastropods, such as Chicoreus virginineus , Phalium glaucum , Rapana rapiformis , and Tonna dolium ( Babu, Venkatesan, & Rajagopal, 2011 ).…”
Section: Health Benefits and Nutritive Values Of Molluscs Of Estuarinmentioning
confidence: 64%
See 2 more Smart Citations
“…The fatty acid composition, especially PUFA contents along with DHA and EPA were previously reported in the various gastropods, particularly in the snails ( Brazao et al, 2003 , Lah et al, 2016 ). Gastropods were found to possess various minerals, such as potassium, sodium, selenium, zinc, iron, and sulfur ( Lah et al, 2016 ). Also, the essential amino acid components were considerably higher in the gastropods, such as Chicoreus virginineus , Phalium glaucum , Rapana rapiformis , and Tonna dolium ( Babu, Venkatesan, & Rajagopal, 2011 ).…”
Section: Health Benefits and Nutritive Values Of Molluscs Of Estuarinmentioning
confidence: 64%
“…Usually, visceral tissues in the larger gastropods were not recommended for consumption, and the foot tissues were typically consumed by the people ( Saito & Aono, 2014 ). Therefore, the previous studies concluded that the foot tissues were suitable for human diet, due to higher protein and lesser lipid contents ( Lah et al, 2016 ). The fatty acid composition, especially PUFA contents along with DHA and EPA were previously reported in the various gastropods, particularly in the snails ( Brazao et al, 2003 , Lah et al, 2016 ).…”
Section: Health Benefits and Nutritive Values Of Molluscs Of Estuarinmentioning
confidence: 99%
See 1 more Smart Citation
“…[39,54,55]). Although we did not obtain measures for the protein content of the Peringia used in our experiments, molluscs are generally recognized as being a protein-rich food (range 50% to greater than 80% protein by dry weight) [56][57][58]. Furthermore, in other studies, knots have been kept on diets of Peringia for extended periods (three to 12 months) [16, 54,59], with no evidence of loss of body condition, as would be expected if this food was low in protein.…”
Section: (B) Experimental Proceduresmentioning
confidence: 99%
“…Recent advances in environmental physiology have shown that ocean changes can also alter biochemical properties of seafood, including proximate composition: i.e., proteins (Tate et al, 2017), lipids (Anacleto et al, 2014;Ab Lah et al, 2017;Tate et al, 2017), and vitamin and mineral contents (López et al, 2010). These changes in biochemical properties can affect nutritive value, and possibly palatability and organoleptic quality (i.e., taste, smell, texture, appearance) of harvested species supporting important fisheries and coastal community economy.…”
Section: Introductionmentioning
confidence: 99%